Update on the development of lurasidone as a treatment for patients with acute schizophrenia - Yasui-Furukori N (Dove Medical Press, 2012)
Norio Yasui-FurukoriDepartment of Neuropsychiatry, Hirosaki University School of Medicine, Aomori, JapanAbstract: Lurasidone is a novel benzisothiazole antipsychotic drug for the treatment of schizophrenia. Of the antipsychotic drugs, lurasidone has the highest affinity for the 5-hydroxytryptamine (5-HT)7 receptor. Lurasidone also has high affinities for the dopamine D2, 5HT2A, 5-HT1A and α2C adrenergic receptors. Moreover, lurasidone has low affinities for the α1 adrenergic, histamine H1 and muscarinic M1 receptors. The involvement of 5-HT7 receptors in cognitive processes has been suggested by both pharmacological and molecular investigations. Chronic treatment with lurasidone increases neurotrophin BDNF mRNA levels in both the hippocampus (ventral and dorsal) and prefrontal cortex under basal conditions or in response to an acute swim stress. Lurasidone may potentiate N-methyl-D-aspartate receptor (NMDAR) function through antagonistic action on 5-HT7 receptors without a direct affinity for NMDARs. These results suggest that lurasidone treatment may be a novel approach for the prevention of the development of cognitive impairment in individuals who are at risk for schizophrenia or related disorders involving cognitive impairment. In clinical trials, treatment with lurasidone was associated with significantly greater endpoint improvement versus placebo on the Positive and Negative Syndrome Scale total score after 6 weeks among subjects receiving 80 or 160 mg. The most frequent side effects of lurasidone were akathisia, nausea, parkinsonism, dizziness and somnolence. Once-daily treatment with lurasidone at 160 mg was superior to placebo based on the composite cognitive functioning measure. Lurasidone treatment produced improvements in Montgomery–Asberg Depression Rating Scale scores at 6 weeks that were significantly greater than placebo. A limitation of this review is that the majority of the data were obtained from abstracts and posters. These sources have not been subjected to the peer review processes of medical journals; thus, the results presented in these forums may require further quality review and subsequent revision prior to final publication.Keywords: lurasidone, antipsychotic, schizophrenia, 5-HT7, cognition, BDNF